2021
DOI: 10.1007/s11301-021-00213-0
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of cash holdings literature: current status, development, and agenda for future research

Abstract: Despite the growing interest in exploring the cash holding aspects among scholars, systematic reviews and comprehensive evaluation in this area has been limited. Also, there is only a fragmented understanding about how the cash holdings concept is formed among researchers and experts. We fill this gap in the literature by identifying and evaluating the research development of cash holdings topic. Using 874 articles from the Scopus database that were published between 1947 and early 2020, bibliometric and conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 135 publications
(195 reference statements)
0
62
0
5
Order By: Relevance
“…This study designed a review protocol as an illustrative guide for SLR development (see, Busalim & Hussin, 2016;Khatib, Abdullah, Hendrawaty & Elamer, 2021) to understand and apply the recommendations' basic rules of studies that take the same approach (Kitchenham, 2004). It has been suggested that having a protocol helps formulate the main research questions, the study synthesis process, the research strategy, the division of studies according to the specific considerations, and the synthesis of the extracted data (Kitchenham & Charters, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…This study designed a review protocol as an illustrative guide for SLR development (see, Busalim & Hussin, 2016;Khatib, Abdullah, Hendrawaty & Elamer, 2021) to understand and apply the recommendations' basic rules of studies that take the same approach (Kitchenham, 2004). It has been suggested that having a protocol helps formulate the main research questions, the study synthesis process, the research strategy, the division of studies according to the specific considerations, and the synthesis of the extracted data (Kitchenham & Charters, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, satisfying stakeholders' desires also spares companies from further pressures that they may face, in addition to working to narrow the legitimacy gap between stakeholders and companies (Al Amosh and Mansor, 2020). So, the issues related to sustainability fall within stakeholders' interests (Khatib et al, 2021;H€ orisch et al, 2020), and this gives companies an excellent opportunity to gain trust and enhance legitimacy.…”
Section: Introductionmentioning
confidence: 99%
“…Another selection of keywords might have shown different results (Delafenestre 2019). Second, we relied only on the Scopus database as it is considered the most leading database of peer-reviewed articles, conference proceedings, and book chapters (Khatib et al 2021). Third, the "Matthew Effect" may also have led to biased findings, when highly cited papers are blindly cited without checking their quality (Luther et al 2020;Ball and Tunger 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This software was developed by the Leiden University Centre for the Science and Technology Studies in the Netherlands. This software is based on an algorithm called "visualization of similarities" or VOS ( Van Eck and Waltman 2020;Lulewicz-Sas 2017;Sarkar and Searcy 2016) The VOSviewer software can present the thematic flow of knowledge and identifying information clusters of the analyzed bibliographic data by possessing common characteristics of authors, countries, documents, affiliations, and occurrence of words (Moed 2010;Zhu et al 2009;Khatib et al 2021;Radicchi et al 2004;Li et al 2020).…”
Section: Methodsmentioning
confidence: 99%